New Pension Insurance Catch-Up Factor in the Mixture of Protection and Level Protection Clauses - Uwe Schätzlein (Wirtschaftsdienst)
Abstract The catch-up factor was suspended in the course of the introduction of the level protection clause in the statutory pension insurance. In order to put an end to this unsatisfactory situation, the Federal Ministry of Labour and Social Affairs has now presented a draft bill outlining how it envisions the reintroduction of the catch-up factor for the pension adjustment in 2022. The reintroduction is a good step. However, given the interplay with the level protection clause, the draft is not yet mature. Moreover, they have included a lock-in clause, which is a big burden. It raises a new problem, the scale of which is similar to that of the suspended catch-up.